ACCUFLOW : commercialization deal - Basant, Rakesh; Karthik, D. (London : Indian Institute of Management, Ahmedabad, 2015)
On March 31, 2005, Professor P. R Dev, Chairperson of Centre for Innovation, Incubation and Entrepreneurship (CIIE) at the Indian Institute of Management (IIM)-Ahmedabad , felt happy about the offer made by Mr. K Paintal, Managing Director, Trio Pharmaceuticals to market the product ACCUFLOW developed by one of their incubatee companies, Exotic Technologies. CIIE was setup in the year 2002 at the Indian Institute of Management Ahmedabad (IIMA), a premier management institute with support from Gujarat Government and Department of Science and Technology, Government of India, to promote innovation and entrepreneurship in India. In Prof. Dev's opinion, Mr. Paintals's offer validated that CIIE could not only identify good innovative products but also facilitate their commercialization. There was however, a lingering doubt in his mind as to whether this commercialization offer and Trio as a partner was the best CIIE could manage for ACCUFLOW.
Originally published in Basant, R., & Karthik, D. (2015). ACCUFLOW: Commercialization deal. CIIE0005. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Indian Institute of Management, Ahmedabad; Consolidation and merger of corporations -- India; Strategic planning; Success in business